Carbon Smart Strategies for Enhanced Food System Resilience Under a Changing Climate - Yeboah, Stephen; Owusu Danquah, Eric; Oteng-Darko, Patricia; Agyeman, Kennedy; Tetteh, Erasmus Narteh (Frontiers in Sustainable Food Systems, 2021)
There is an urgent need to match food production with increasing world population through identification of sustainable land management strategies. However, the struggle to achieve food security should be carried out keeping in mind the soil where the crops are grown and the environment in which the living things survive, especially under rainfed agricultural system. Rainfed agricultural ecosystem is extremely fragile, improving soil fertility and reducing greenhouse gas emission are key factors for developing sustainable agriculture. This paper addresses the effects of carbon smart technologies on greenhouse gas emission, soil quality and crop productivity in rainfed agro ecological environment. Carbon smart technologies highlighted in this paper include minimum tillage, crop residue retention, agroforestry, biofuels, integrated nutrient management and land use management systems. This paper review and discusses the work done on carbon smart technologies in different agro-ecological regions so as to understand its impact from the perspectives of the soil, the crop and the environment. A detailed case study of the strength of the carbon smart technologies in improving soil and crop productivity in Ghana is highlighted immensely. Finally, this paper discussed tremendous advancements that have been made towards more efficient and sustainable agriculture for improved food system.